VERBALIZATION SUFFIXES {–IZE} {–IFY}, {–ATE}, AND {–EN} IN ENGLISH AND THEIR EQUIVALENCES IN INDONESIAN - Masrul Huda (Teaching English as a Foreign Language Overseas Journal, 2023)
The objective of the study is to find the distribution of the suffixes in forming the verbs in English. Then, to find the equivalence for each suffix in Indonesian. The method used in writing is descriptive qualitative. Some ways are conducted in gaining the result such as providing data from Oxford Dictionary and then bilingual dictionary by John Echols and Hasan Shadily (2008) used as the guidance in translating the words. The analysis used is translational method. The results are (1) suffix {ize} has some equivalences to prefix {me-}, prefix {ber-}, affix {me-kan}, and affix {memper-kan}. (2) The equivalences of suffixx {-ify} are prefix {me-}, affix {memper-}, and affix {me-kan}. The third suffix {-ate} has some equivalences to prefix {me-}, affix {memper-}, affix {me-kan}, and affix {me-i}, then suffix {-en} will be prefix {me-}, affix {me-kan}, affix {me-i}, and affix {memper-}.